Feeding gelatinized carbohydrate in the diets of magur, Clarias batrachus (Linnaeus, 1758): Effects on growth performance, enzyme activities and expression of muscle regulatory factors. (13th December 2018) - Talukdar, Avinash; Kumar, Sarvendra; Varghese, Tincy; Jain, Kamal K.; Sahu, Narottam P.; Sahoo, Sujata
Abstract: This study was conducted to illustrate the effect of dietary gelatinized starch (GS) on the growth performance, enzyme activities and expression of MyoD and Myf5 in magur, Clarias batrachus fingerlings. Four iso‐nitrogenous (37%) and iso‐lipidic (6%) diets containing 15% (D‐1), 25% (D‐2), 35% (D‐3) or 45% (D‐4) GS were fed to 240 fingerlings (2.5 ± 0.5 g) in triplicates groups for 8 weeks. The maximum weight gain %, specific growth rate, protein efficiency ratio, lower FCR and higher mRNA expression of MyoD or Myf5 were found in the D‐3 group fed with 35% GS. Higher hepatosomatic index, viscerosomatic index, body lipid and lower moisture content were found in the D‐4 group. Aspartate transaminase and alanine transaminase activities were found to be higher in the D‐1 group. Amylase, glucose‐6‐phosphate dehydrogenase and blood glucose were higher in the D‐4 group. Superoxide dismutase, catalase and hexokinase activities remain unaffected by the dietary GS levels. Hence, the overall results indicate that 35% GS can improve growth performance and upregulate myogenic regulatory factors, but 45% GS level will favor lipogenesis and compromise growth. Furthermore, Myf5 gene showed more immediate response than the MyoD to the dietary carbohydrate in magur.